PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS GAMBAR PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP UNTUK SMP - Wilandari, Putri Ayu; Ardi, Ardi; Risdawati, Renny (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The source that is used by student in science learning proses is studentâs worksheet (LKS). Studentâs worksheet that available in SMPN 29 Padang is made or designed by MGMP Teacherâs science, which is that studentâs worksheet does not have the interest design. The picture yhat is given on worksheet does not have color and less clear. Picture instruction and picture still less clear. The material in science learning at eight grade in SMP about humanâs growth and development. Based on this case, this research has purpose to make studentâs worksheet (LKS) that have validity and simple picture on the human growth and development material for SMP. This research had done in SMPN 29 Padang at eight grade, on January academic year 2013/2014. This research is development research, about development on studentâs worksheet that have 4-dimension picture model which is modified, they are define, design, and development. The data of research is primary data, includes validity and practical that is analyzrd by descriptive analysis is percentage. The studentâs worksheet (LKS) has validity value is 80,75%. It means that is acceptted by validator based on didactic, construction, and also technique. It has result practical value around 78,60% from teacher, and 81,98% student that resultis named practical the conclusion that studentâs worksheet (LKS) is validity and practical